Abnehmende Bedeutung der Lagerinvestitionen für den Konjunkturverlauf? - Jörg Döpke; Enno Langfeldt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
– With the widespread application of inventory control Systems in industry and trade and a fast growing Services sector the influence of inventory changes on the business sector should become less important over time. However, the empirical eyidence for Germany in the period 1970-1994 shows that especially at cyclical turning-points inventory fluctuations continue to have a major impact on overall oütput. Additional research süggests that inventones in Germany are not part of the monetary transmission mechanism but work as an accelerator when there is a turnaround in final demand.
Keywords: E32; E37; 330; Inventories; business cycles; Lagerinvestition; Lagerzyklus; Konjunktur; Akzelerator; Konjunkturprognose; Deutschland